Research on the support of the brewing ecological characteristics of strong-flavor Baijiu to brewing microecology - LU Xingfei, XIE Ruilin, QIN Hui, ZHOU Jun, LIU Shuangping, CAI Xiaobo, DAI Yu, ZHAO Xiaobo, HUANG Mengyang, ZHANG Suyi (Zhongguo niangzao)
The eco-geographical conditions of the three regions located at 28° north latitude (Luzhou, Nanchang and Taizhou city) were compared using remote sensing technology, and the microbial community structure of the environment inside and outside the workshop was analyzed using high- throughput sequencing technology, and the microorganisms in the distiller's grains were traced through SourceTracker quantitative analysis. The analysis results of ecological geographical conditions showed that Luzhou city had the highest average annual humidity (82.76%), the shortest annual sunshine duration (1 166 h) and the lowest annual average wind speed (1.74 m/s), the soil was acidic and humid, and the water quality was superior, which was conducive to the growth and propagation of microorganisms. It showed that the formation of strong-flavor Baijiu was closely related to its unique ecological and geographical conditions. The microbial community structure analysis of the brewing workshop indicated that there were certain differences in the dominant microorganisms across different workshops, and the microbial community structure also varied between the internal and external environments of the same workshop. Furthermore, there were interactive effects among the microorganisms. The results of microbial traceability analysis showed that Daqu was the main source of microorganisms in distiller's grains, with the contribution rate of fungi ranging from 40.53%-73.28%, and the contribution rate of bacteria was 49.23%. The microorganisms also came from the surface of equipment and tools, the air and the ground, indicating that the microorganisms in the brewing area of strong-flavor Baijiu were one of the important sources of microorganisms in distiller's grains.